Partial microglial depletion and repopulation exert subtle but differential effects on amyloid pathology at different disease stages - L. H. D. Le; M. K. O’Banion; A. K. Majewska (Scientific Reports, 2024)
Abstract Colony-stimulating factor-1-receptor (CSF1R) inhibitors have been widely used to rapidly deplete microglia from the brain, allowing the remaining microglia population to self-renew and repopulate. These new-born microglia are thought to be “rejuvenated” and have been shown to be beneficial in several disease contexts and in normal aging. Their role in Alzheimer’s disease (AD) is thus of great interest as they represent a potential disease-modifying therapy. Here, we explored the differential effects of microglial depletion and repopulation during amyloid pathology progression using 5xFAD mice. We utilized the CSF1R inhibitor PLX3397 to induce microglial self-renewal and tracked microglia-plaque dynamics with in vivo imaging. We observed transient improvement in plaque burden on different timescales depending on the animal’s age. While the improvement in plaque burden did not persist in any age group, renewing microglia during mid- to late-pathology might still be beneficial as we observed a potential improvement in microglial sensitivity to noradrenergic signaling. Altogether, our findings provide further insights into the therapeutic potential of microglial renewal in AD.